The Implementation of Deeper Learning in Fiqh Instruction within the Merdeka Curriculum at Islamic Elementary School - Aida Hayani; Akhmad Zulfikar Khabibullah; Moh. Farhan; Putri Nabila; Fifi Anti Mapika Sari binti Sukamto (Alma Ata University Press, 2026)
The implementation of the Merdeka Curriculum has encouraged a paradigm shift from teacher-centered instruction to student-centered learning that promotes higher-order thinking skills, character development, and lifelong learning. Despite these expectations, Fiqh instruction in Islamic Elementary Schools (Madrasah Ibtidaiyah) continues to encounter several pedagogical challenges. Consequently, an instructional approach that facilitates meaningful, reﬂective, and engaging learning experiences is required to optimize the implementation of the Merdeka Curriculum. This study investigates the implementation of the Deeper Learning approach in Fiqh instruction and examines its contribution to improving learning quality at MIN Kota Lhokseumawe. Employing a qualitative ﬁeld research design, participants were selected using purposive sampling, involving the principal, one Fiqh teacher, and students who were directly engaged in the implementation of Deeper Learning in classroom instruction.The collected data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing and veriﬁcation, while the trustworthiness of the ﬁndings was established through source triangulation, method triangulation, and member checking. The data were analyzed using thematic analysis following the interactive model of Miles, Huberman, and Saldaña, involving data condensation, data display, and conclusion drawing and veriﬁcation. The ﬁndings demonstrate that Deeper Learning transforms conventional Fiqh instruction into an active learning process that encourages inquiry, collaboration, reﬂection, and contextual understanding.. However, challenges remain, including diﬀerences in students' learning readiness, limited instructional media, and the need for continuous teacher adaptation to innovative instructional approaches. The study concludes that integrating Deeper Learning into the Merdeka Curriculum enhances not only students' conceptual understanding of Fiqh but also their critical thinking, collaboration, communication, and character development, making it a promising pedagogical approach for improving Islamic education at the elementary level.